A unified approach to thermo-mechano-caloric-characterization of elastocaloric materials - Franziska Louia; Nicolas Michaelis; Andreas Schütze; Stefan Seelecke; Paul Motzki (JPhys Energy, 2023)
This paper presents a novel approach to characterizing the relevant mechanical, thermal and caloric properties of elastocalorics material in a single testing device. Usually, tensile experiments are performed to determine the rate- and process-depending stress/strain behavior of nickel-titanium-based shape memory alloys and potentially other elastocaloric materials made from metallic alloys. These tests are relevant for, e.g., characterization of hysteresis properties and subsequent calculation of mechanical work input. In addition, simultaneous observation with an infrared camera is useful to understand temperature evolution and maximum temperature changes achievable during the loading/unloading process. Characterization of the caloric properties of the materials determines latent heats and, together with the mechanical work, also the material coefficient of performance. It is typically carried out via differential scanning calorimetry (DSC), which is performed in a separate device and requires a second experiment with different types of samples. Furthermore, DSC measurements do not reflect the way mechanically induced phase transformations trigger the release and absorption of latent heats as it is the case for elastocalorics. In order to provide a more consistent understanding of the relevant elastocaloric material properties, we here present a novel method that (a) allows for a systematic determination of load-dependent latent heats and (b) introduces a comprehensive testing setup and suitable testing routine to determine the mechanical, thermal and caloric parameters in the same experimental device and with the same sample, thus greatly simplifying the overall procedure.